Gallbladder cancer - Vivas, Carlos; Ferreira, Carlos; Czarnevicz, Daniel; Cidade, Luis; Caviglia, Pablo; Silva, Celso; Secondo, Gerardo; Misa, Carlos; Leites, Alejandro; Torterolo, Edgardo (Cirugía del Uruguay, 1995)
Gall-bladder cancer is general/y considered an incurable disease. lt has been possible to obtain better results late/y by means of the knowledge of the evo/ution of the disease and the determina/ion of subgroups of more favourable prognosis. The aim of this paper is to try to determine the factors that inf/uence long-term survival by making a retrospective analysis of patients operated on far ga/1-bladder cancer during 1 O years in a General Surgery Service. The 1987 TNM classification system of the lnternational Union against Cancer was employed. Ga/1-bladder cancer corresponded to 3% of 1500 cholecystectomies; average age was 59. lncidence of ga/1-bladder cancer in cholecystectomy pieces rose with age: average age far stage I was 58 years, 62 years far stage JI, 64 years far stage /JI and 70 years far stage IV. The fo/lowing procedures were carried out: 26 simple cholecystectomies, 6 radical cholecystectomies (medial hepatectomy and dissection of hepatic pedicle, retroduodenopanchreatic and celiac artery), 3 cholecystostomies, 2 transtumoral intubations and 9 explorative laparotomies. There was 8% global morbility and 11 % mortality These figures rose to 30% and 0% far radical surgery. The survival far patients who underwent radical surgery was of 100% and 80% at 2 and 3 years respective/y There were no data on cholecystectomy follow-ups. The authors conclude that there is not an homogeneous prognosis in the case of ga/1-bladder cancer patients. Tumors in early stages, with a high degree of differentiation which -are general/y diagnosed in patients under 60 benefit from radical surgery and obtain satisfactory long-term survival rates.